2022
DOI: 10.1097/01.nurse.0000872424.15581.b0
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysreflexia

Abstract: A patient with a spinal cord injury presented to our clinic with signs and symptoms that our staff did not recognize. It was later determined to be autonomic dysreflexia. What is important to know about autonomic dysreflexia?-GE, GA Julianne Mercado, RN; Amanda Ruiz, RN; and Bridget Parsh, EdD, RN, CNS respond-Autonomic dysreflexia (AD), also known as autonomic hyperreflexia, is a potentially life-threatening acute syndrome that occurs in 20% to 70% of patients with spinal cord injury (SCI) at or above the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Noxious stimuli below the level of the SCI trigger an exaggerated sympathetic nervous system response from T6 to L2 due to posttraumatic cord hypersensitivity and a lack of compensatory parasympathetic stimulation. Diffuse vasoconstriction occurs below the level of the SCI, typically, in the lower two-thirds of the body, and can cause a severe rise in BP 2,4. This rise in BP normally stimulates the baroreceptors in the carotid sinus and aortic arch, triggering a parasympathetic response to slow the heart rate by stimulating the vagal nerve and causing vasodilation.…”
Section: Pathophysiology Of Admentioning
confidence: 99%
See 3 more Smart Citations
“…Noxious stimuli below the level of the SCI trigger an exaggerated sympathetic nervous system response from T6 to L2 due to posttraumatic cord hypersensitivity and a lack of compensatory parasympathetic stimulation. Diffuse vasoconstriction occurs below the level of the SCI, typically, in the lower two-thirds of the body, and can cause a severe rise in BP 2,4. This rise in BP normally stimulates the baroreceptors in the carotid sinus and aortic arch, triggering a parasympathetic response to slow the heart rate by stimulating the vagal nerve and causing vasodilation.…”
Section: Pathophysiology Of Admentioning
confidence: 99%
“…However, the spinal cord lesion blocks the parasympathetic response. Although vasodilation occurs above the SCI, uncontrolled vasoconstriction occurs below it 2,4. This uncontrolled sympathetic response can cause retinal hemorrhage, seizures, stroke, pulmonary edema, or cardiac arrest 5,6…”
Section: Pathophysiology Of Admentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] AD can lead to potentially lifethreatening consequences such as hemorrhagic stroke, myocardial infarction, and pulmonary edema. 14,15 Controlled release 2:1 ratio oxycodone hydrochloride/naloxone hydrochloride (OXN; Targinâ, Purdue Pharma) is approved for use by Health Canada (DIN 02387425; DIN 02339609; DIN 02339617; DIN 02339625) for the treatment of severe chronic pain and has potential to ameliorate side effects such as OIC which can improve treatment adherence. 16 Studies have shown that OXN can prevent or reduce OIC, while maintaining the analgesic effects of oxycodone.…”
Section: Introductionmentioning
confidence: 99%